Ácido hexanóico como uma alternativa ao cobre na proteção de citrus contra infecção de Xanthomonas citri - Caccalano, Mario Nicolas [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Brazil is one of the largest orange producers in the world and is the world leader in the production of sweet oranges. Asian citrus canker (ACC) is one of the most worrying bacterial diseases for the agricultural industry in Brazil. ACC is caused by the Gram-negative bacterium Xanthomonas citri subsp. citri (X. citri), which affects several cultivated citrus varieties of economic interest and for which there is no cure. According to the new legislation to control ACC, São Paulo is a risk mitigation area (RMA), therefore, ACC control is exercised by planting less susceptible cultivars, the use of copper-based formulations, installation windbreaks in order to prevent the spread of the bacteria, which spreads through the combined action of wind and rain. Copper is bioaccumulative and toxic and bacterial strains resistant to this metal have been reported. Thus, the objective of this work was to evaluate the potential of hexanoic acid as a possible alternative to copper in the fight against citrus canker. The hexanoic acid had an IC90 of 123.8ppm and an IC50 of 96.33ppm. The compound was considered bacteriostatic at 125 ppm, as there was growth in the MBC assay. The hexanoic acid was bactericidal at 250 ppm. The compost did not interfere with the total number of seeds germinated at concentrations up to 300 ppm and there was no reduction in the germination index up to 200 ppm. In protective tests, at a concentration of 400ppm, a decrease in the number of cancer lesions was observed, suggesting a protective effect. In microscopic analysis, no alteration was seen either in the integrity of the bacterial membrane or in the formation of dividing septa in the groups treated with the acid. Finally, we defined the safety concentration (400ppm) through a resistance induction test.

Brasil é um dos maiores produtores de laranja do mundo e é líder mundial em produção de laranjas doce. O cancro cítrico asiático (ACC) é uma das doenças bacterianas mais preocupantes para a citricultura no Brasil. ACC é causada pela bactéria Gram-negativa Xanthomonas citri subsp. citri (X. citri), que afeta diversas variedades cultivadas de citros de interesse econômico e para a qual não existe cura. De acordo com a nova legislação para controle da ACC, São Paulo é uma área de mitigação de risco (SMR), desta forma, controle de ACC é exercida mediante plantio de cultivares menos susceptíveis ao cancro, uso de formulações a base de cobre, instalação de quebra-vento em pomares com o intuito de se evitar a disseminação da bactéria, que se espalha pela ação combinada de ventos e chuva. Cobre é biocumulativo e tóxico e resistência bacteriana a este metal já foi relatada em linhagens de X. citri. Desta maneira, o objetivo do trabalho foi avaliar o potencial do ácido hexanóico como uma possível alternativa ao cobre no combate do cancro cítrico. O ácido hexanóico apresentou uma IC90 de 123,8 ppm e IC50 de 96,33ppm. O composto foi considerado bacteriostático em 125 ppm, visto que houve crescimento no ensaio de MBC. O ácido hexanóico foi bactericida a 250 ppm. O composto não interferiu com o número total de sementes germinadas em concentrações de até 300 ppm e não houve redução no índice de germinação em até 200 ppm. Em testes protetivos, em concentração de 400ppm, foi observada uma diminuição no número de lesões de cancro, sugerindo um efeito protetivo. Em analises de microscopia não foi visto nenhuma alteração tanto na integridade da membrana bacteriana quanto na formação de septos de divisão nos grupos tratados com o ácido. Por fim, definimos a concentração de segurança (400ppm) por meio de um ensaio de indução de resistência.
Hexanoic acid as an alternative to copper in protecting citrus against Xanthomonas citri infection
Keywords: Phytopathogenic microorganisms; Bioactive compounds; Microbiology; Microorganismos fitopatogênicos; Compostos bioativos; Microbiologia